The individual decision-making process of refugees in Yogyakarta - Rory John Brown (Economic Journal of Emerging Markets, 2016)
The imminent situation faced by asylum seekers is a crucial factor in understanding their decision making process. This study has adopted Bronfenbrenner’s ecological model to map out the circumfix of influence affecting refugees in Yogyakarta. In particular, this study makes use of rational choice, social strain and migration theory to better understand individual choice. Through the scope of behavioural analysis, this study finds that asylum seekers arriving in Indonesia begin utilising legal avenues of refugee migration and resettlement to a third party state once their ecological setting became more stable.